What futures for the people of the tropical forests? - Byron, R.N.; Arnold, J.E.M. (1999)
The importance of forest products to households living in or near forests has been increasingly recognized. Estimates of numbers of people who in some way rely on forests, for survival or livelihoods, vary widely. Yet numbers alone do not reveal the forests' importance to diverse users. A typology that recognizes the varied relationships of people to forests and forest products permits assessment of the impacts of economic, cultural, and social changes. Understanding these relationships is crucial for institutions to adapt to changing patterns of demand, use, and supply, and to support both "forest-dependent" and "forest-related" peoples.